(untitled) (Marketing Journal, 2025)
This article analyzes the economic indicators of railway transport and considers issues of increasing the efficiency of transport services in the conditions of Uzbekistan. Measures aimed at increasing the efficiency of transport services are studied. The article considers important aspects of international and local experiences. It also presents statistical data on the volume of freight and passenger transportation of railwa y transport, revenue growth and cost efficiency. It highlights the priority areas of state policy for the modernization of transport infrastructure and improving the 101 quality of services. Based on international and local experience, proposals and recommenda tions aimed at increasing economic efficiency are developed .